Em Nome do “Pai”, do “Filho” e do Espírito de Corpo: Ou como recordar a provável 1ª Edição da Cartilha do Guerrilheiro da UNITA - Fidel Reis (Cadernos de Estudos Africanos)
This text presents a reflexive contribution concerning the configuration and structuring process of UNITA as a political-military organization, having as reference a document found in the Torre do Tombo archives entitled 1ª Edição da Cartilha do Guerrilheiro da “UNITA”, dated 1968, whose authorship is attributed to Jonas Savimbi. It was possible to glimpse, in the mentioned Cartilha do Guerrilheiro, a discursive production that might refer to a process of construction of an organizational identity sustained, not only by a mobilizing belief (revolutionary nationalism) but also by a logic of functioning based on the principle of discipline. Hence we have formulated the following question: to what extent can the Cartilha do Guerrilheiro be apprehended as an instrument of ideological and identity construction of the organization UNITA, and which place the principle of discipline occupies in this dynamic of construction?